2021
DOI: 10.3389/fpubh.2021.691851
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Barriers and Enablers to Physical Activity Among Older Adults

Abstract: Despite its well-known health benefits, most older adults do not commit to undertaking sufficient physical activity (PA). In this study we aimed to examine the perceived benefits of and barriers and enablers to PA from the perspectives of older Caucasian and Chinese adults living in Australia. Individual and group interviews with 17 Caucasian (mean age: 72.8 years) and 47 Chinese adults (mean age: 74.0 years) were conducted and analysed using thematic analysis. Overall, participants knew about the benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Exercise self-efficacy mean scores improved significantly from 25.2 ± 5.8 (median 25 [21,29]) at CR entry to 26.2 ± 6.3 (median 27 [22,31]) at completion. The mean difference from CR entry to completion was 0.96 (95% CI, 0.12-1.80, P = .025).…”
Section: Exercise Self-efficacy Scoresmentioning
confidence: 95%
See 2 more Smart Citations
“…Exercise self-efficacy mean scores improved significantly from 25.2 ± 5.8 (median 25 [21,29]) at CR entry to 26.2 ± 6.3 (median 27 [22,31]) at completion. The mean difference from CR entry to completion was 0.96 (95% CI, 0.12-1.80, P = .025).…”
Section: Exercise Self-efficacy Scoresmentioning
confidence: 95%
“…Furthermore, lower levels of physical activity insufficient to meet international recommendations are often reported by patients from ethnic minorities, women, and those from lower socioeconomic status 19,20. These differences may be explained, at least in part, by complex systemic barriers known to be experienced by these populations,16 as well as individual factors such as lower levels of self-motivation and confidence to exercise 21. Spousal or partner support may also contribute to the promotion of self-efficacy to exercise because partners can remind, encourage, and support the other person to follow an exercise regimen that can be undertaken in the home environment both during and after CR 22…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The motivators and barriers for a healthy lifestyle among older adults with a migration background remain relatively unstudied, especially for older women. Only a few studies demonstrated differences in motivators and barriers for physical activity among older adults (65 years and older) between ethnic groups in America and Australia [23,24], but these studies did not specifically focus on women or differentiated according to sex. A recent focus group study in the Netherlands demonstrated that Moroccan-Dutch women (aged 44 to 60 years) have a different perception of healthy lifestyles and health compared to older native Dutch women [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given their experience of migrating to and resettling in a new country, sociocultural changes might also impact on how they respond to dementia, such as seeking diagnosis and care support. For example, language difficulties were often reported as a barrier to social and health service access in CALD populations (Batalova, 2012;You et al, 2021).…”
Section: Introductionmentioning
confidence: 99%